Context, time, and change: Historical approaches to entrepreneurship research - Wadhwani, R. Daniel; Kirsch, David; Welter, Friederike; Gartner, William B.; Jones, Geoffrey G. (Strategic Entrepreneurship Journal, 2020)
Research Summary We articulate the value of historical methods and reasoning in strategic entrepreneurship research and theory. We begin by introducing the papers in the special issue, contextualizing each within one of five broader methodological approaches, and elaborating on the applicability of each to other topics in entrepreneurship research. Next, we use the papers to induce a framework for integrating history into entrepreneurship theory. The framework demonstrates how historical assumptions play a formative role in operationalizing time and context in entrepreneurship research. We then show how variations in these treatments of time and context shape theoretical claims about entrepreneurial opportunities, actions, and processes of change. We conclude by discussing why this may be a particularly opportune time for strategic entrepreneurship research to develop a deeper historical sensibility. Managerial Summary History can serve as an especially important guide to understanding entrepreneurship during moments of change. We draw on articles from the special issue on “Historical Approaches to Entrepreneurship Research” to illustrate different forms of historical reasoning and research about entrepreneurship. Moreover, we use the articles to develop a framework for understanding how historical context and time shape entrepreneurial opportunities, actions, and processes of change. We emphasize, in particular, the value of history in understanding variations in entrepreneurial practices.